Determining Tourism Area Using TOPSIS Analysis in the Dampier Strait Conservation Area - Anisa Kusumadewi Zulfikar Zulfikar; Yonvitner Yonvitner; Fery Kurniawan; Adrian Hidayat (Postgraduate, University of Mataram, 2024)
The Dampier Strait regional conservation area is one of the conservation areas included in the Raja Ampat Regency marine conservation area, which has high potential for developing tourism activities. The most important aspect in the use of natural resources for tourism purposes is their suitability to support tourism activities. The challenge faced is the difficulty if the potential for beach tourism, snorkeling and diving to be developed simultaneously. The aim of this research is to determine areas for ecotourism and recommend appropriate locations. Data analysis is determining ecotourism areas using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). TOPSIS is used because it is able to rank the selected alternatives that are closest to the positive ideal and furthest from the negative ideal solution. The criteria used are tourist carrying capacity, accommodation, accessibility, number of international tourists, number of domestic tourists and suitability area. The results of this TOPSIS analysis are that Sauwandarek, Marandanweser and Arborek are areas that can be used as an alternative area for carrying out beach tourism, snorkeling and diving activities. Areas that can be developed into ecotourism activities are Yeben Kecil and Tanjung Putus.